2021
DOI: 10.32615/ps.2021.032
|View full text |Cite
|
Sign up to set email alerts
|

Role of beneficial elements in plants: implications for the photosynthetic process

Abstract: Car -carotenoids; Chl -chlorophylls; Ci -intercellular CO2 concentration; Cyt b6/f -cytochrome b6f complex; E -transpiration rate; ETR -electron transport rate; Fm -maximum chlorophyll fluorescence yield; Fv/Fm -maximum photochemical efficiency of PSII; gm -mesophyll conductance; gs -stomatal conductance; Jmax -maximum rate of electron transport; NPS -nanoparticles; OEC -oxygen-evolving complex; PN -net assimilation of photosynthesis; qP -photochemical quenching coefficient; ROS -reactive oxygen species; Vcmax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…However, the coordination of Me n+ with two O atoms of the carboxylate groups of PCs is also possible, e.g., in p -coumaric acid [ 207 ]; Universal affinity of PCs in relation to different Me n+ in both cationic and anionic forms: During the systematizing of the experimental and literature data, we revealed that PC ligands from various subgroups form complexes with 69 Me n+ ions (63 chemical elements; Table 1 , Figure 1 ). Binding to PCs is a characteristic of/universal for the elements differing in their roles in plants: Essential macronutrients (Ca, Mg, K) and essential micronutrients (Fe, Mn, Zn, Ni, Cu, B, Mo), which are necessary for the plant life cycle, cannot be substituted by other elements and are directly involved in plant metabolism [ 208 ]; Beneficial elements (Al, Co, Na, Se) that promote the growth of various plant species, but are not essentially required for the completion of the plant life cycle [ 209 , 210 ]; Non-essential metal(loid)s that are not involved in primary plant metabolism; Rare earth elements (REEs), which include the lanthanide group with 15 elements ( Figure 2 ). The complexation of PC ligands with 11 elements essential for human life (Na, Mg, K, Ca, Mn, Fe, Co, Cu, Zn, Mo, Se) has also been confirmed [ 211 ].…”
Section: Plant Phenolics As Ligands For Metal(loid)smentioning
confidence: 99%
See 1 more Smart Citation
“…However, the coordination of Me n+ with two O atoms of the carboxylate groups of PCs is also possible, e.g., in p -coumaric acid [ 207 ]; Universal affinity of PCs in relation to different Me n+ in both cationic and anionic forms: During the systematizing of the experimental and literature data, we revealed that PC ligands from various subgroups form complexes with 69 Me n+ ions (63 chemical elements; Table 1 , Figure 1 ). Binding to PCs is a characteristic of/universal for the elements differing in their roles in plants: Essential macronutrients (Ca, Mg, K) and essential micronutrients (Fe, Mn, Zn, Ni, Cu, B, Mo), which are necessary for the plant life cycle, cannot be substituted by other elements and are directly involved in plant metabolism [ 208 ]; Beneficial elements (Al, Co, Na, Se) that promote the growth of various plant species, but are not essentially required for the completion of the plant life cycle [ 209 , 210 ]; Non-essential metal(loid)s that are not involved in primary plant metabolism; Rare earth elements (REEs), which include the lanthanide group with 15 elements ( Figure 2 ). The complexation of PC ligands with 11 elements essential for human life (Na, Mg, K, Ca, Mn, Fe, Co, Cu, Zn, Mo, Se) has also been confirmed [ 211 ].…”
Section: Plant Phenolics As Ligands For Metal(loid)smentioning
confidence: 99%
“…Beneficial elements (Al, Co, Na, Se) that promote the growth of various plant species, but are not essentially required for the completion of the plant life cycle [ 209 , 210 ];…”
Section: Plant Phenolics As Ligands For Metal(loid)smentioning
confidence: 99%
“…This is particularly relevant when managing beneficial elements in agriculture. Aluminium (Al), cobalt (Co), selenium (Se), silicon (Si), and sodium (Na), when supplied to plants in low or limited concentrations (such as the ones promoted within sustainable agriculture), can bring beneficial outcomes in certain crops, such as growthpromoting effects [14]. Hence, they are not considered essential elements for species to survive but have an important role in plant biology, including the ability to balance the toxicity and the beneficial effect of one another, as is the case of Al and Si or Na [15].…”
Section: Figurementioning
confidence: 99%
“…Thereafter, elements in the plant also play great role in formation of secondary metabolites and other physiological functions. Many repots revealed the significant role of elements in physiological function and proper growth of the plant's vis a vis improvement of the bioactive components in the plant body which further enhances the therapeutic or medicinal properties (Kheyrkhah et al, 2018;Lo Piccolo et al, 2021). Based on the concept, the present study was carried out with the herbal plant.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%